Analysis of dynamic protein carbonylation in rice embryo during germination through AP‐SWATH. Issue 6 (March 2016) - Zhang, Hui; He, Dongli; Yu, Jianlan; Li, Ming; Damaris, Rebecca Njeri; Gupta, Ravi; Kim, Sun Tae; Yang, Pingfang
Abstract : Seed germination is an important aspect of the plant life cycle, during which, reactive oxygen species (ROS) accumulate. The accumulation of ROS results in an increase in protein oxidation of which carbonylation is the most canonical one. However, there is insufficient information concerning protein oxidation, especially carbonylation and its contribution to seed germination. In this study, biotin hydrazide labeled chromatography combined with sequential window acquisition of all theoretical fragment ion spectra (SWATH) method was used to analyze the dynamic pattern of protein carbonylation in rice embryos during germination. A total of 1872 unique proteins were quantified, among which 288 carbonylated peptides corresponding to 144 proteins were determined based on the filtering through mass shifts of modified amino acids. In addition, 66 carbonylated proteins were further analyzed based on their carbonylation intensity in four stages of germination. These identified carbonylated proteins were mainly involved in maintaining the levels of ROS, abscisic acid and seed reserves. Remarkably, a peroxiredoxin was found with 23 unique carbonylated peptides, and the expression of which was consistent with its increased activity. This study describes the dynamic pattern of carbonylated proteins during seed germination, and may help to further understand the biochemical mechanisms on this process.